Longitudinal tau and metabolic PET imaging in relation to novel CSF tau measures in Alzheimer’s disease - Leuzy, Antoine; Cicognola, Claudia; Chiotis, Konstantinos; Saint-Aubert, Laure; Lemoine, Laetitia; Andreasen, Niels; Zetterberg, Henrik; Ye, Keqiang; Blennow, Kaj; Höglund, Kina; Nordberg, Agneta (European journal of nuclear medicine and molecular imaging, 2019)
Purpose Studies comparing CSF and PET tau biomarkers have included only commercial CSF assays examining specific phosphorylation sites (e.g. threonine 181, P-tau 181p ) and mid-domain tau (i.e. total tau, T-tau). Moreover, these studies did not examine CSF tau levels in relation to cerebral glucose metabolism. We thus aimed to examine CSF tau measures, using both commercial and novel assays, in relation to [ 18 F]THK5317 (tau) and [ 18 F]FDG PET (glucose metabolism). Methods Fourteen Alzheimer’s disease (AD) patients (seven prodromal, seven dementia) underwent [ 18 F]THK5317 and [ 18 F]FDG PET studies, with follow-up performed in ten subjects (six prodromal, four dementia) after 17 months. In addition to commercial assays, novel measures capturing N-terminus+mid-domain (tau N-Mid) and C-terminally truncated (tau-368) fragments were included. Results While the levels of all forms of CSF tau were found to be inversely associated with baseline [ 18 F]FDG uptake, associations with baseline [ 18 F]THK5317 uptake varied in relation to the degree of isocortical hypometabolism ([ 18 F]FDG SUVR). Changes in the levels of the novel CSF markers tracked longitudinal changes in tracer uptake better than changes in P-tau 181p and T-tau levels, and improved concordance with dichotomized regional [ 18 F]THK5317 measures. Conclusion Our findings suggest that neurodegeneration may modulate the relationship between CSF and PET tau biomarkers, and that, by comparison to P-tau 181p and T-tau, tau-368 and tau N-Mid may better capture tau pathology and synaptic impairment.